The effectiveness of desensitization versus rechallenge treatment in HIV-positive patients with previous hypersensitivity to TMP-SMX: a randomized multicentric study - Bonfanti, P.; Pusterla, L.; Parazzini, F.; Libanore, M.; Cagni, A.E.; Franzetti, M.; Faggion, I.; Landonio, S.; Quirino, T. (Biomedicine & pharmacotherapy, 2000)
Our study was undertaken to evaluate if desensitization treatment is more effective than rechallenge in preventing hypersensitivity reactions in HIV-positive patients with previous allergic reactions to TMP-SMX; the secondary aim was to evaluate the frequency of reactions to TMP alone. This was a randomized, multicentre open study. Patients with previous documented hypersensitivity to TMP-SMX who required primary or secondary PCP prophylaxis were enrolled; subjects who had previously had serious adverse reactions to TMP-SMX were excluded. All eligible patients assumed 200 mg TMP for 14 days and in case of no reactions were randomized for desensitization or rechallenge with TMP-SMX. The patients were then followed up by periodical visits for six months. Seventy-three patients were enrolled; 14 subjects (19%) presented reactions on TMP alone during the pre-enrollment phase. The remaining 59 subjects were randomly assigned to the two treatment groups: 34 carried out desensitization (group 1) and 25 rechallenge (group 2) with TMP-SMX. Seven patients in group 1 (20.5%) and seven in group 2 (28%) showed hypersensitivity reactions during treatment; this difference was not statistically significant. No serious reaction occurred in either group. This study showed the comparable effectiveness of the desensitization procedure and rechallenge in patients with a previous, not serious, allergic reaction to TMP-SMX.